Pengaruh Gaya Kepemimpinan terhadap Kinerja Pegawai pada Dinas Peternakan, Kesehatan Hewan, dan Perikanan Kabupaten Soppeng - Muhammad Saqil; Nurjannah Nurjannah (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
The low performance produced by employees in carrying out their duties and work is thought to be related to the leadership style applied at the Soppeng Regency Livestock, Animal Health and Fisheries Service. These factors are variables that need to be studied in this research so that the influence of leadership style on the performance of employees of the Department of Animal Husbandry, Animal Health and Fisheries in Soppeng Regency can be determined. The aim of this research is: To determine the influence of leadership style on employee performance at the Department of Livestock, Animal Health and Fisheries, Soppeng Regency. This research was carried out at the Department of Livestock, Animal Health and Fisheries, Soppeng Regency, which is located on Jalan Salotungo Watansoppeng, Lalabta Rilau Village, Lalabata District, Soppeng Regency. So the samples in this study were all 24 employees of the Soppeng Regency Animal Husbandry, Animal Health and Fisheries Service. To determine the effect of leadership style on employee performance, simple linear regression analysis was used. From the results of a simple regression analysis, it can be concluded that: Leadership style has a significant influence on employee performance at the Soppeng Regency Livestock, Animal Health and Fisheries Service. The suggestions given by researchers to the Soppeng Regency Animal Husbandry, Animal Health and Fisheries Service, are to maintain and improve the leadership style currently applied so that the performance of Soppeng Regency Animal Husbandry, Animal Health and Fisheries Service employees.